2019
DOI: 10.7150/jca.31156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel methylated DNA marker ZNF569 for head and neck squamous cell carcinoma

Abstract: Aberrant DNA methylation pattern plays an indispensable role in the initiation and development of head and neck squamous cell carcinoma (HNSCC). It is well recognized that lymph node metastasis is closely with unfavorable prognosis of HNSCC. Therefore, exploring the methylation events accounting for the lymph node metastasis of HNSCC is very important for improving the clinical outcome of HNSCC. Methylation data, RNA-seq data and clinical data were downloaded from The Cancer Genome Atlas (TCGA) and processed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Interestingly, we showed that ZNF569me levels could discriminate between ECa and normal esophagus with high specificity, regardless of the histotype, extending those previous reports. Furthermore, ZNF569 me was shown to play a tumor-suppressive role in head and neck squamous cell carcinoma [ 35 ] and a DNA-methylation based panel, which included ZNF569me , discriminated gastric adenocarcinoma from normal mucosa [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we showed that ZNF569me levels could discriminate between ECa and normal esophagus with high specificity, regardless of the histotype, extending those previous reports. Furthermore, ZNF569 me was shown to play a tumor-suppressive role in head and neck squamous cell carcinoma [ 35 ] and a DNA-methylation based panel, which included ZNF569me , discriminated gastric adenocarcinoma from normal mucosa [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC) is the sixth most common cancer around the world, and squamous cell carcinoma (HNSCC) accounts for more than 90% of all HNC cases [1,2]. It represents a leading reason for cancer-attributable morbidity and mortality, with a global incidence of 550 000 cases and 380 000 deaths annually [3].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we showed that ZNF569me levels could discriminate between ECa and normal esophagus with high speci city, regardless of the histotype, extending those previous reports. Furthermore, ZNF569me was shown to play a tumor-suppressive role in head and neck squamous cell carcinoma (36) and a DNA-methylation based panel, which included ZNF569me, discriminated gastric adenocarcinoma from normal mucosa (37).…”
Section: Discussionmentioning
confidence: 99%